SOCIAL REFORMS INITIATED BY SREE CHATTAMPI SWAMIKAL IN KERALA (International Journal of Food and Nutritional Sciences, 2022)
Sree Chattampi Swamikal (1853-1924) was a revered sage and social reformer in Kerala during the late 19th century. Alongside his contemporary, Narayana Guru, he aimed to transform the heavily ritualistic and caste-bound Hindu society of that era.Swamikal questioned rigid interpretations of Hindu texts, emphasizing compassion and inclusivity. His mission was to liberate Hinduism from excessive ritualism and caste-based restrictions.Swamikal actively worked for women's emancipation, encouraging their participation in public life.He believed in breaking free from societal constraints. Swamikal promoted vegetarianism as a way to foster compassion and respect for all living beings.His commitment to non-violence extended beyond dietary choices. Swamikal believed that different religions were diverse paths leading to the same ultimate truth.He facilitated dialogue and understanding among followers of various faiths. Chattampi Swamikal maintained friendships across Kerala, enriching his life intellectually and spiritually. He authored several books on spirituality, history, and language..Chattampi Swamikal's legacy continues to inspire generations, urging them to question norms, champion equality, and seek spiritual enlightenment.